Natural Antimicrobial Peptides: Pleiotropic Molecules in Host Defense - Sanchez, Mercedes Leonor (2013)
Natural antimicrobial peptides (AMPs) are small cationic molecules that display antimicrobial activity against a wide range of bacteria, fungi and viruses. AMPs are multifunctional molecules that have an essential activity in infection and inflammation: they play an important role in the innate immune response, not only as antimicrobial agents, but also as immunomodulating molecules and as an important link between the innate and adaptive immune response. In this article, we will discuss the antimicrobial activity, together with the novel properties of some of these molecules as immune modulators on the innate and adaptive immune response.